Strategies for managing spring frost risks in orchards: effectiveness and conditionality—A systematic review protocol - Bianca Drepper; Brecht Bamps; Anne Gobin; Jos Van Orshoven (Environmental Evidence, 2021)
Abstract Background Spring frosts pose an important threat to orchard productivity in temperate zones and predictions of future occurrences do not exclude damaging events. However, there is no up-to-date and systematic comparison of the effectiveness and conditionality of the existing passive and active damage prevention strategies. This review seeks to answer the questions “How do the performances of spring frost damage reduction strategies in temperate fruit orchards compare?” and “How do environmental conditions affect frost damage reduction strategies in temperate fruit orchards?”. Methods and output The review covers on-site frost damage prevention mechanisms and interventions for the most important temperate pome, stone and citrus fruit trees as well as grapevine. Searches include the core collection and regional databases on the Web of Science platform, Scopus, as well as specialized libraries like Agris, Agricola, CAB Abstracts, Groenekennis and selected institutional websites. Included studies report on the effectiveness of at least one intervention in reducing spring frost damage or increasing temperatures in the field. The validity of the studies will be evaluated based on their risk of general research bias and on topic-specific, stakeholder co-designed validity criteria. Data will be extracted regarding the study setup (study design, location, characteristics of frosts) and the resulting temperature increase, crop development alteration and/or damage reductions. The effectiveness of interventions will be evaluated in terms of yields, damage to flowers, ambient temperature and/or crop development. An Evidence Atlas will identify general and geographic research gaps, as well as research trends. Meta-regression of effectiveness on environmental conditions will be attempted.